Electrospun biomaterial scaffolds with varied topographies for neuronal differentiation of human‐induced pluripotent stem cells. Issue 8 (30th December 2014) - Mohtaram, Nima Khadem; Ko, Junghyuk; King, Craig; Sun, Lin; Muller, Nathan; Jun, Martin Byung‐Guk; Willerth, Stephanie M.
Abstract In this study, we investigated the effect of micro and nanoscale scaffold topography on promoting neuronal differentiation of human induced pluripotent stem cells (iPSCs) and directing the resulting neuronal outgrowth in an organized manner. We used melt electrospinning to fabricate poly (ε‐caprolactone) (PCL) scaffolds with loop mesh and biaxial aligned microscale topographies. Biaxial aligned microscale scaffolds were further functionalized with retinoic acid releasing PCL nanofibers using solution electrospinning. These scaffolds were then seeded with neural progenitors derived from human iPSCs. We found that smaller diameter loop mesh scaffolds (43.7 ± 3.9 µm) induced higher expression of the neural markers Nestin and Pax6 compared to thicker diameter loop mesh scaffolds (85 ± 4 µm). The loop mesh and biaxial aligned scaffolds guided the neurite outgrowth of human iPSCs along the topographical features with the maximum neurite length of these cells being longer on the biaxial aligned scaffolds. Finally, our novel bimodal scaffolds also supported the neuronal differentiation of human iPSCs as they presented both physical and chemical cues to these cells, encouraging their differentiation. These results give insight into how physical and chemical cues can be used to engineer neural tissue. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2591–2601, 2015.